2018
DOI: 10.1038/s41559-018-0552-0
|View full text |Cite
|
Sign up to set email alerts
|

Origin and maintenance of chemical diversity in a species-rich tropical tree lineage

Abstract: Plant secondary metabolites play important ecological and evolutionary roles, most notably in the deterrence of natural enemies. The classical theory explaining the evolution of plant chemical diversity is that new defences arise through a pairwise co-evolutionary arms race between plants and their specialized natural enemies. However, plant species are bombarded by dozens of different herbivore taxa from disparate phylogenetic lineages that span a wide range of feeding strategies and have distinctive physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
161
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(165 citation statements)
references
References 51 publications
4
161
0
Order By: Relevance
“…However, a recent study of M. melissa performance on a related plant, Medicago truncatula , found that genetic variation in the plant explained a substantial proportion of phenotypic variation (between 8% and 57%) in phytochemical and structural traits but also in caterpillar performance (Gompert et al, 2019). Of course, most plants do not have the luxury of optimizing defense against a single herbivore, and it is easy to imagine that improvements in defense against one enemy could lead to increased attraction to another (Salazar et al, 2018), especially given the diversity of effects even within major classes studied here, including saponins and phenolic glycosides. Compounds in the latter class (phenolics) were found to have strong positive and negative effects on assemblages of arthropods associated with the maternal plants from which seeds were collected to start the common garden used in the present study (Harrison et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study of M. melissa performance on a related plant, Medicago truncatula , found that genetic variation in the plant explained a substantial proportion of phenotypic variation (between 8% and 57%) in phytochemical and structural traits but also in caterpillar performance (Gompert et al, 2019). Of course, most plants do not have the luxury of optimizing defense against a single herbivore, and it is easy to imagine that improvements in defense against one enemy could lead to increased attraction to another (Salazar et al, 2018), especially given the diversity of effects even within major classes studied here, including saponins and phenolic glycosides. Compounds in the latter class (phenolics) were found to have strong positive and negative effects on assemblages of arthropods associated with the maternal plants from which seeds were collected to start the common garden used in the present study (Harrison et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We found that tree-level polyphenol composition covaried with the community structure of sessile insects. The chemical composition of plant tissue has recently been recognized as an important factor explaining plant-associated insect diversity both between (Abrahamson et al 2003, Richards et al 2015, Salazar et al 2018) and within species (Poelman et al 2010, Glassmire et al 2016, Bustos-Segura et al 2017, but exactly what drives the observed phenotypic variation in plant chemistry is often not known.…”
Section: Tree-level Chemical Composition Covaried With Insect Communimentioning
confidence: 99%
“…By analogy between communities of biological species and mixtures of phytochemicals, these metrics have been used to quantify the variation in phytochemical diversity across plant samples and assess how that variation is linked to key ecological and evolutionary variables (e.g. Kursar et al ; Richards et al ; Bustos‐Segura et al ; Salazar et al ). Complementing this empirical work, several recent reviews have greatly advanced our conceptual understanding of phytochemical diversity by summarising its evolutionary causes, biochemical origins and ecological consequences (Dyer et al ; Moore et al ; Schuman et al ; Dyer et al ; Kessler & Kalske ; Lämke & Unsicker ).…”
Section: Introductionmentioning
confidence: 99%